DOP89 Final growth in paediatric Crohn's disease is impaired also in the era of biologics: a population-based analysis from the epiIIRN administrative cohort. (25th January 2019) - Assa, A; Cohen, S; Asayag, N; Dan, N; Focht, G; Ledder, O; Lederman, N; Matz, E; Cahan, A; Balicer, R; Feldman, B; Brufman, I; et al.
Abstract: Background: The diagnosis of Crohn's disease (CD) during childhood is associated with a high rate of growth impairment. The contemporary rate of impaired final height is, however, less known in the era of biologics. We aimed to explore the final height of children diagnosed with IBD before the age of 12 years and during the biologics era. Methods: New paediatric CD cases were identified within the epiIIRN database, a validated registry of all IBD patients in the Israeli national health maintenance organisations (HMOs), covering 98% of the Israeli population. Height and height velocity measurements were retrieved from the electronic charts and transformed into age- and sex-matched z-scores according to the WHO reference standards. Results: In total, 1365 children were diagnosed with IBD under the age of 12 years during 2005–2017; 902 had CD of whom 346 reached the age of 18 years by time of analysis (55.5% males, mean age at diagnosis 9.7 ± 1.8). The height difference between CD children and the reference standards steadily decreased over the years: from Δ5.7 cm (z score=−0.83 95% CI [−0.92, −0.74]) at age 12 to Δ3 cm (z=−0.45 [−0.54, −0.36]) at age 18 years in females, and from Δ 2.4 cm (z=−0.33 [−0.4, −0.27]) to Δ3.92 cm (z=−0.52 [−0.6, −0.45]) in males. Similarly, the rate of females with height <1 and <2 SD of the general population mean decreased from 40.3% and 13% at age 12 years to 25.1% and 6.9% at 18 years, respectively. The corresponding rates of <1 and <2 SD in males were 27.3% and 4.9% at age 12 years and 27.30% and 6.82% at age 18. Eventually, both males and females with CD were significantly shorter at the age of 18 years than the general population (173.2 ± 7.6 cm vs. 176.1 ± 7.5 and 160 ± 11.5 vs. 163 ± 6.6, respectively; p < 0.0001). The final height of 463 children with UC at the age of 18 years was similar to the general population (z-score of females −0.0048 95% CI [−0.2, 0.19] and of males −0.1347 [−0.39, 0.122]). Height velocity in CD and UC patients from age 12 to 18. Conclusions: This population-based analysis shows that 25.1% of females and 27.3% of males diagnosed with CD in the biologics era do not attain normal final adult height while 6.9% of females and 6.8% of males have a substantially reduced height. This study was supported by a grant from the Leona M. and Harry B. Helmsley Charitable Trust.